POTENTIAL OF USING LOCAL WISDOM IN MATHEMATICAL PROBLEM POSING E-MODULE: A NEED ANALYSIS - Kertiyani, Ni Made Intan; Lu'luilmaknun, Ulfa; Azmi, Syahrul (Mathematics Education And Application Journal (META), 2023)
Problem posing become one of the essential skills to promote in class. Meanwhile, there is still limited research on electronic teaching materials that integrated local wisdom to enhance student problem posing. The aim of this research is to investigated the perception of teacher about problem posing and the need to include local wisdom in electronic module. This research is descriptive research. The teachers who have implemented and have not implemented the teaching material to foster problem posing in Lombok Island, Indonesia become the subject of this study. The data was collected by questionnaire and interview. The questionnaire contains subject’s perception about problem posing and their need to integrate local wisdom in e-module. The data was analyzed by statistic descriptive and qualitative method. The majority of teachers believe that students need to enhance their problem posing skill. Furthermore, they require educational resources based on local wisdom, such as the Rinjani Geopark, to strengthen that skill. The findings of this study recommended that the development of an e-module to promote problem posing could be the next area of investigation..Keywords: problem posing, local wisdom, need analysis, teaching material, e-module. Kemampuan mengajukan pertanyaan (problem posing) menjadi salah satu kemampuan yang perlu dimiliki siswa di kelas. Namun, studi mengenai bahan ajar elektronik yang memfasilitasi pengembangan kemampuan ini masih terbatas. Penelitian ini bertujuan untuk menginvestigasi persepsi guru mengenai kemampuan problem posing dan kebutuhan mengenai bahan ajar elektronik untuk meningkatkan kemampuan ini dengan mengintegrasikan kerifan lokai di Pulau Lombok, Indonesia. Penelitian ini merupakan penelitian deskriptif. Subjek penelitian adalah guru yang sudah dan belum pernah mengajar menggunakan bahan ajar yang berorientasi pada peningkatan kemampuan problem posing. Data diperoleh dari kuisioner dan wawancara. Kuisioner berisi pertanyaan untuk menggali persepsi subjek mengenai problem posing dan kebutuhannya mengenai bahan ajar elektronik yang mengintegrasikan kearifan lokal. Data dianalisis menggunakan statistika deskriptif dan metode kualitatif. Mayoritas subjek guru meyakini bahwa siswa perlu meningkatkan kemampuan problem posing-nya. Lebih jauh, mereka memerlukan sumber belajar berdasarkan kearifan lokal sepergi Geopark Rinjani untuk memperkuat kemampuan tersebut. Selanjutnya, konstruksi bahan ajar elektronik untuk meningkatkan kemampuan ini menjadi potensi studi yang dapat diteliti.Kata kunci: problem posing, kearifan lokal, analisis kebutuhan, bahan ajar, modul elektronik.